Cannabidiol-based natural health products for companion animals: Recent advances in the management of anxiety, pain, and inflammation. (November 2021) - Yu, Cindy H.J.; Rupasinghe, H.P. Vasantha
Abstract: Recent advances in cannabidiol (CBD) use in canines and felines for anxiety management, pain management, and anti-inflammatory effects were reviewed using a literature search conducted with the following keywords: CBD, anxiety, inflammation, pain, dogs, cats, and companion animals. For decades, research on CBD has been hindered due to the status of cannabis ( C. sativa L.) as an illicit drug. Limited safety data show that CBD is well-tolerated in dogs, with insufficient information on the safety profile of CBD in cats. Upon oral supplementation of CBD, elevation in liver enzymes was observed for both dogs and cats, and pharmacokinetics of CBD are different in the two species. There is a significant gap in the literature on the therapeutic use of CBD in cats, with no feline data on anxiety, pain, and inflammation management. There is evidence that chronic osteoarthritic pain in dogs can be reduced by supplementation with CBD. Furthermore, experiments are required to better understand whether CBD has an influence on noise-induced fear and anxiolytic response. Preliminary evidence exists to support the analgesic properties of CBD in treating chronic canine osteoarthritis; however, there are inter- and intra-species differences in pharmacokinetics, tolerance, dosage, and safety of CBD. Therefore, to validate the anxiety management, pain management, and anti-inflammatory efficacy of CBD, it is essential to conduct systematic, randomized, and controlled trials. Further, the safety and efficacious dose of CBD in companion animals warrants investigation. Highlights: The cannabis plant has a wide array of therapeutic benefits in humans and animals. Cannabidiol (CBD) is the minimally-psychoactive bioactive molecule in cannabis. The safety, efficacy, and pharmacokinetics of CBD in animals have been scarce. The potential of CBD on the management of anxiety, pain, and inflammation in companion animals has been reviewed.